2016
DOI: 10.3346/jkms.2016.31.8.1292
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of Diabetic Retinopathy in Patients with Type 2 Diabetes Correlates with the Presence and Severity of Coronary Heart Disease

Abstract: Both diabetic retinopathy (DR) and coronary heart disease (CHD) are clinically significant in diabetic patients. We investigated the correlation between the severity of DR and the presence and severity of CHD among type 2 diabetic patients. A total of 175 patients who were examined at the DR clinic and underwent dual-source computed tomography (DSCT) angiography within 6 months were included. The degree of DR was graded as no DR, nonproliferative DR (NPDR), and proliferative DR (PDR). The severity of CHD and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…Our results were agreed with results from Um et al [10] . They reviewed 175 sheets of patients records retrospectively, patients were classified into three groups according to the severity of DR, 38 patients had DR, and 88 non-proliferative DR, and 49 with proliferative DR.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were agreed with results from Um et al [10] . They reviewed 175 sheets of patients records retrospectively, patients were classified into three groups according to the severity of DR, 38 patients had DR, and 88 non-proliferative DR, and 49 with proliferative DR.…”
Section: Discussionsupporting
confidence: 94%
“…A marked association has appeared between those measures of microvascular damage and CAD not only in the general population but also in cohorts with diabetes, suggesting potential reflection of that retinal measures captured from retinal photographs, reflecting generalized microvascular disease, on further refining of CAD risk in diabetics [9] .. Recent studies had suggested that retinopathy is considered an early sign of other vascular complications, being highly associated with development of CAD [10] . This is propped by previous studies that linked retinopathy signs with more ischemic T-wave changes on electro-cardiogram, coronary perfusion defects, poorer coronary flow reserve and lower coronary collateral scores, than those without retinopathy [11] .…”
Section: Diabetic Retinopathy [Dr]mentioning
confidence: 99%
“…Such information is necessary in order to facilitate timely intervention, development of preventative procedures, and for the planning of future screening services for DR. Additionally, the presence of DR could also be considered an indicator of microcirculatory dysfunction in other vital organs in the body as well as in the eye (21). Some studies suggest that the presence of DR may be linked to an increased risk of systemic vascular complications, such as coronary heart disease, stroke and nephropathy (22)(23)(24)(25)(26). Therefore, an increase in awareness of DR and its risk factors will enable better comprehension of systemic diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study reported that PDR has no additional effect to classical CAD risk factors to identify CAD in T2D patients. 29 Although there is still noise on effect of PDR over traditional CV risk factors, possibly because of differences in the exposures compared ( e.g ., nonproliferative DR vs. PDR), and diagnosis of CAD ( e.g ., computed tomography angiography vs. coronary angiography).…”
Section: Discussionmentioning
confidence: 99%